1984
DOI: 10.2307/1590145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Inactivated Mycoplasma gallisepticum Oil-Emulsion Bacterins for Protection against Airsacculitis in Broilers

Abstract: Broiler chicks were vaccinated subcutaneously in the neck at various ages with a single 0.5-ml dose of beta-propiolactone-inactivated Mycoplasma gallisepticum (MG) oil-emulsion bacterin. Four weeks later, vaccinated and control chicks were placed in cold environmental cabinets, infected with infectious bronchitis virus intratracheally, and 2 days later challenged by aerosol exposure to live MG broth culture. All chicks were killed 21 days later and scored postmortem for the rate and severity of airsacculitis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However, the analysis of the M. gallisepticum levels showed that the logarithm of the AUC in the vaccinated pairs was 0.51 Table 1. Q-PCR and serology results of the non-vaccinated and vaccinated groups Although this is first report where the horizontal transmission of M. gallisepticum among vaccinated birds has been quantified, the indication of a reduction in M. gallisepticum shedding is in agreement with earlier studies (Hildebrand et al ., 1983;Yoder et al ., 1984;Kleven, 1985;Talkington & Kleven, 1985;Withear, 1996). This finding prompted several authors to hypothesize that vaccination might have a long-term effect, eventually stopping horizontal transmission (Talkington & Kleven, 1985;De Nie & Goren, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…However, the analysis of the M. gallisepticum levels showed that the logarithm of the AUC in the vaccinated pairs was 0.51 Table 1. Q-PCR and serology results of the non-vaccinated and vaccinated groups Although this is first report where the horizontal transmission of M. gallisepticum among vaccinated birds has been quantified, the indication of a reduction in M. gallisepticum shedding is in agreement with earlier studies (Hildebrand et al ., 1983;Yoder et al ., 1984;Kleven, 1985;Talkington & Kleven, 1985;Withear, 1996). This finding prompted several authors to hypothesize that vaccination might have a long-term effect, eventually stopping horizontal transmission (Talkington & Kleven, 1985;De Nie & Goren, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…An experimental inactivated oil emulsion MG bacterin prepared by Yoder et al (1984) was also capable of protecting 11-to 14-day-old chickens against experimental challenge. Our present TS MG vaccine with adjuvant was effective as well.…”
Section: Isolation Ofmg From the Air Sacsmentioning
confidence: 99%
“…Chickens inoculated with vaccine emulsified in adjuvant all developed a high level of antibody (Panigrahy et ah, 1981;Hildebrand et al, 1983;Glisson and Kleven, 1984;Yoder et al, 1984). However, the titres of serum antibody and the levels of protection might not be related (McMartin and Adler, 1961;Hayatsu et al, 1974;Lam and Lin, 1984b).…”
Section: Isolation Ofmg From the Air Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological lesions in the air sac were evaluated according to the scoring system described by Yoder et al (1984).…”
Section: Data Collectedmentioning
confidence: 99%